Halal value chain integration in food court establishment through Cash Waqf Linked Sukuk: evidence from Indonesia - Widya Sartika Hasibuan; Irsad Lubis (Cogent Business & Management, 2024)
The monitoring of upstream and downstream halal standards is crucial for Indonesia due to its large Muslim population and the increasing global demand for halal products. Indonesia has the potential to become a leading center for the Sharia economy and finance. Thus, developing the halal food and Islamic finance sectors is one strategy to unlock their potential, while strengthening the halal-value chain ecosystem further aids the expansion of the halal food industry. Therefore, this study aims to develop the halal food sector and the Islamic financial sector by integrating the halal value chain into the establishment of a food court financed through the Cash Waqf Linked Sukuk (CWLS) Islamic financial instrument. This study used qualitative methods with primary and secondary data sources. The primary data came from observations and interviews with the Indonesian Waqf Board (BWI). While the secondary data used in this study includes research findings regarding the Halal Value Chain as well as the framework for the application of CWLS funds. The result shows that accelerating the establishment of a halal food court ecosystem can be implemented through CWLS funding. This framework offers financial assistance while maintaining the halal status of food court management. This study provides suggestions to the government on how to enhance the halal ecosystem for Indonesia's halal ecosystem improvement.
Keywords: 650; Cash Waqf Linked Sukuk; cash waqf; food court; halal value chain; ijarah; Indonesia